2015
DOI: 10.1159/000382079
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Longevity after a Spinal Cord Injury: Systematic Review and Meta-Analysis

Abstract: Background/Aims: Mortality and longevity studies of spinal cord injury (SCI) are essential for informing healthcare systems and policies. This review evaluates the current evidence among people with SCIs worldwide in relation to the WHO region and country income level; demographic and lesion characteristics; and in comparison with the general population. Methods: A systematic review of relevant databases for original studies. Pooled estimates were derived using random effects meta-analysis, restricted to traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
103
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 102 publications
(268 reference statements)
9
103
0
2
Order By: Relevance
“…Mortality rates between 2-and 3-times that of the GP have been regularly reported in recent SCI literature [3]. Unfortunately, despite advances in medical technology and rehabilitation, a multitude of studies have found only limited or no improvement in long-term mortality [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mortality rates between 2-and 3-times that of the GP have been regularly reported in recent SCI literature [3]. Unfortunately, despite advances in medical technology and rehabilitation, a multitude of studies have found only limited or no improvement in long-term mortality [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic spinal cord injuries (TSCIs), comprised within the assemblage of neurological diseases, are a disabling condition associated with reduced functioning and quality of life, increased morbidity, and reductions in life expectancy. In comparison to the general population, persons with TSCI have a roughly 2.5 times greater risk of mortality (standardized mortality ratio [SMR] 2.5, 95% CI 1.9-3.2) [3]. This burden of mortality is similar to what has been estimated for other chronic neurological conditions such as multiple sclerosis (SMR 2.8, 95% CI 2.7-2.9) [4] or traumatic brain injury (SMR 2.3; 95% CI 2.1-2.4) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like many unforeseen medical emergencies, a TSCI could lead to early death in the absence of essential emergency and acute care (7, 8). Hence, the single most important indicator of the quality of medical care is reflected in short- and long-term mortality (9).…”
Section: Introductionmentioning
confidence: 99%
“…1 SCI and associated health problems lead to premature mortality and increased risk for lower physical and mental health compared to the general population. 1,2 In interaction with environmental factors and personal resources, an SCI may lead to lower participation in social and economic activities. 3,4 As a result, the lived experience of persons with SCI has increasingly become the focus of research, going beyond the description of one's health state into domains of functioning and disability, as characterized by the WHO's International Classification of Functioning, Disability and Health (ICF) 5 and summarized in the International Perspectives on SCI (IPSCI) report.…”
mentioning
confidence: 99%